1989
DOI: 10.1111/j.1532-950x.1989.tb01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracodorsal and Caudal Superficial Epigastric Axial Pattern Skin Flaps in Cats

Abstract: Nonselective angiography, selective angiography, and gross dissection of 15 cadavers were performed to delineate direct cutaneous arteries in the cat. The omocervical, deep circumflex iliac, thoracodorsal, and caudal superficial epigastric arteries were identified by nonselective angiography. Selective angiography and gross dissection allowed assessment of the origin and vascular territories of the thoracodorsal and caudal superficial epigastric arteries. Orthotopic and heterotopic transfers of thoracodorsal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
8

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 9 publications
2
52
1
8
Order By: Relevance
“…The combination of omentalization and thoracodorsal flap led to successful healing of a chronic axillary wound in this and in other studies (Lascelles and White, 2001). In another cat of the present study an axillary wound was successfully managed with a thoracodorsal flap with no omentalization (Remedios et al, 1989;Lascelles and White, 2001).There are no studies however, to compare thoracodorsal flap alone and thoracodorsal flap combined with omentalization in cats. Therefore both techniques seem to provide favorable outcomes in cats for reconstruction of chronic axillary wounds.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The combination of omentalization and thoracodorsal flap led to successful healing of a chronic axillary wound in this and in other studies (Lascelles and White, 2001). In another cat of the present study an axillary wound was successfully managed with a thoracodorsal flap with no omentalization (Remedios et al, 1989;Lascelles and White, 2001).There are no studies however, to compare thoracodorsal flap alone and thoracodorsal flap combined with omentalization in cats. Therefore both techniques seem to provide favorable outcomes in cats for reconstruction of chronic axillary wounds.…”
Section: Discussionmentioning
confidence: 94%
“…It is reported that in cats with shorter limbs in relation to their torso length caudal superficial epigastric flaps can be extended below the tibiotarsal joint (Remedios et al, 1989, Remedios et al, 1991. Caudal superficial epigastric flaps elevated as island flaps have increased mobility and can provide coverage to the metatarsal region (Remedios et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have rich perfusion and an increased rate of survival (96-100%) (Remedios et al, 1989;Aper and Smeak, 2003;2005). When compared to subdermal plexus flaps with equal dimensions, they have 50% more possibilities for survival 1993;Wardlaw and Lanz, 2012).…”
Section: Reconstructive Techniques I Skin Flapsmentioning
confidence: 99%